The Harm of a Label: The effect of Party Affiliation upon Criminal Sentencing in the United States - Day, Jane Frances (2012)
This thesis examines why sentencing disparity between partisan elected and non-partisan elected judiciaries exists. I contend that partisan elected judiciaries produce harsher sentences. The theoretical reasoning provided, is that political parties converge to the mean on politically popular issues, in this case a perceived “toughness on crime”. Therefore party affiliation and party primary selection causes judicial officers to conform their sentencing practices to party demands in order to gain selection, election and retention. I conducted a quantitative analysis of the conviction and imprisonment data from circuit courts in geographically and demographically similar counties of Illinois (partisan election) and Michigan (non-partisan election) to test this theory. In my case study this severity of sentence is measured by the number of criminal convictions that result in imprisonment. The partisan elected judiciary produced significantly higher rates of imprisonment, suggesting that party affiliation is a contributing factor to sentencing disparity between judicial selection systems